An organizational ecology approach to EGTC creation in East Central Europe. Issue 1 (1st January 2020) - Telle, Stefan; Svensson, Sara
ABSTRACT: European Groupings of Territorial Cooperation (EGTC) are a legal instrument intended to facilitate institutional cross-border cooperation. Launched in 2006, EGTC creation was particularly swift in East Central Europe, albeit with significant variation between different border regions. The article adopts an organizational ecology perspective to explain this variation and argues that the level of organizational density inside a cross-border ecological niche is crucial for EGTC creation. The analysis draws on policy documents and semi-structured interviews with key stakeholders from four border areas in East Central Europe. It finds that lower levels of organizational density in unitary states constitute a favourable organizational environment for EGTC creation. However, rather than enhancing autonomous decision-making in the border region, we find evidence that unitary state support for EGTC creation reflects a political strategy to centralize control over cross-border cooperation.